Safety, efficacy, and treatment satisfaction in adults with ITP who switched to avatrombopag from another TPO-RA - Michael D. Tarantino; Kailash Mosalpuria; Scott Kolodny; Jessica Zhang; Michael Vredenburg; Brian D. Jamieson (Blood Advances)
Abstract: This phase 4, multicenter, open-label study was conducted to evaluate the safety, efficacy, and treatment satisfaction of switching to avatrombopag from another thrombopoietin receptor agonist (TPO-RA) in patients with immune thrombocytopenia (ITP). Adults who had received ≥90 days of treatment with eltrombopag or romiplostim and had a response (2 platelet counts [PCs] ≥50 × 109/L) switched to avatrombopag with no protocol-defined washout period. The primary end point was the incidence of treatment-emergent adverse events (TEAEs) and serious TEAEs. Secondary end points were the proportion of patients who had a PC between ≥50 × 109/L and ≤200 × 109/L (days 15, 30, 60, and 90) and change from baseline in each domain of the self-administered Treatment Satisfaction Questionnaire for Medication (TSQM) to day 90. Among 60 enrolled patients, 58.3% experienced TEAEs and 10.0% experienced serious TEAEs (1 related to avatrombopag [thrombocytopenia that resolved]; 5 unrelated [1 unrelated death]). A PC ≥50 × 109/L to ≤200 × 109/L was reported for 51.7%, 31.7% (mean PC, 256.2 × 109/L [standard deviation, 176.7 × 109/L]), 55.0%, 60.0%, and 55.0% at baseline and on days 15, 30, 60, and 90, respectively. TSQM scores increased from baseline to day 90 across all domains (mean change: convenience, +13.5; effectiveness, +14.4; global satisfaction, +14.2; side effects, +8.3). There was no correlation between stable avatrombopag dose (day 90) and previous TPO-RA dose (high or low). Patients with ITP may safely switch from another TPO-RA to avatrombopag and maintain adequate PCs while experiencing improved treatment satisfaction. This trial was registered at www.ClinicalTrials.gov as #NCT04638829